Biotechnology for Wastewater Treatment from Textile Enterprises in the Bukhara Region - Bo’riyevich, Bo’riyev Sulaymon; Hamroqulova, Xolliyeva Dilnavoz (American Journal of Biodiversity, 2025)
Textile enterprises in the Bukhara region significantly contribute to economic development but also generate large volumes of wastewater containing toxic pollutants. Conventional treatment methods often fail to meet environmental standards efficiently. Biotechnology-based approaches, including microbial treatment, enzymatic degradation, and bioaugmentation, offer promising solutions for sustainable wastewater management. This article explores current biotechnological methods applicable to textile wastewater treatment, analyzes their effectiveness in the Bukhara context, and provides recommendations for implementation.